Role of indocyanine green fluorescence and inferior thyroid artery ligation in hypocalcemia after total-thyroidectomy - Enrico Battistella; Luca Pomba; Silvia Rocchi; Giovanna Magni; Riccardo Toniato; Antonio Toniato (Biomolecules & Biomedicine, 2025)
Postoperative hypocalcemia remains a frequent complication of total thyroidectomy, and identifying intraoperative strategies to prevent it continues to be a key clinical challenge. This retrospective study aims to evaluate the role of indocyanine green (ICG) fluorescence imaging and truncal ligation of the inferior thyroid artery in the development of hypocalcemia following total thyroidectomy. Additionally, it seeks to identify factors associated with or predictive of hypocalcemia measured on postoperative day 1, as well as to determine the prevalence of transient and permanent hypoparathyroidism. The study included 200 patients who underwent total thyroidectomy performed by the same surgical team between January 2023 and March 2024. The surgical technique employed involved ligation of the inferior thyroid artery at its proximal trunk. Serum calcium levels were assessed for all patients during hospitalization, and again at 10 and 30 days post-surgery. Additionally, the relationship between postoperative calcemia and the vascularization of at least one parathyroid gland was evaluated using indocyanine green fluorescence imaging. Hypocalcemia (<8.5 mg/dL) was observed in 81 patients (40.5%) on postoperative day 1. The rate of transient hypoparathyroidism was 31% (62 patients), while permanent postoperative hypoparathyroidism was seen in 2.5% (5 patients). Patients with a positive vascularization index on indocyanine green fluorescence imaging were significantly less likely to experience hypocalcemia (Fisher’s exact test, p = 0.0014). The truncal ligation of the inferior thyroid artery did not significantly influence the occurrence of transient or permanent hypoparathyroidism. In conclusion, indocyanine green fluorescence imaging is confirmed as a useful tool for evaluating parathyroid vascularity, although its associated costs should be carefully considered.